2014
DOI: 10.1073/pnas.1322098111
|View full text |Cite
|
Sign up to set email alerts
|

Human breast cancer metastases to the brain display GABAergic properties in the neural niche

Abstract: Dispersion of tumors throughout the body is a neoplastic process responsible for the vast majority of deaths from cancer. Despite disseminating to distant organs as malignant scouts, most tumor cells fail to remain viable after their arrival. The physiologic microenvironment of the brain must become a tumor-favorable microenvironment for successful metastatic colonization by circulating breast cancer cells. Bidirectional interplay of breast cancer cells and native brain cells in metastasis is poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
225
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 268 publications
(240 citation statements)
references
References 49 publications
14
225
1
Order By: Relevance
“…Further, a series of studies demonstrated that BC cells that invaded and seeded into the brain tissue are capable to Bmimic^the phenotype of the neuronal cells by acquiring the ability to utilise the specific neurotransmitter which is the γ-aminobutyric acid (GABA) [47,48]. Consequently, the invading breast cancer cells exhibit specific neural characteristics which enable them to penetrate into the brain tissue; thereby, highly activated GABA expression increases their proliferative capacity, particularly within the pre-metastatic niches as the preferable microenvironment.…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…Further, a series of studies demonstrated that BC cells that invaded and seeded into the brain tissue are capable to Bmimic^the phenotype of the neuronal cells by acquiring the ability to utilise the specific neurotransmitter which is the γ-aminobutyric acid (GABA) [47,48]. Consequently, the invading breast cancer cells exhibit specific neural characteristics which enable them to penetrate into the brain tissue; thereby, highly activated GABA expression increases their proliferative capacity, particularly within the pre-metastatic niches as the preferable microenvironment.…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…Most importantly, breast cancer patient brain metastases exhibit a GABAergic phenotype including the up-regulation of GABA(A) receptors, GABA transporters and GAD expression (16). A putative role for GABA(A) in breast cancer is further supported by the observation that propofol, a multifunctional drug with agonist activity for the GABA(A) receptor, induces actin reorganization and migration of breast cancer cells through collagen matrices (17,18).…”
mentioning
confidence: 98%
“…It was suggested that to metastasize to the brain, tumor cells may escape their normative genetic constraints by coinhabiting the neural niche. Indeed, breast tumor cells metastasizing to the brain were found to display a GABAergic phenotype analogous to that of neurons, indicating a metastasis-promoting effect of coinhabitation of the neuronal niche in the brain (76).…”
Section: Resultsmentioning
confidence: 99%